Effects of Polyamide and/or Phenalkamine Curing Agents on the Jute Fibre Reinforcement with Epoxy Resin Matrix. (2017) - Deepak, P.; Vignesh Kumar, R.; Badrinarayanan, S.; Sivaraman, H.; Vimal, R.
Abstract: From the date, till now, many hardeners were utilized for the purpose of curing epoxy resins at room temperature. Amines, oxides, anhydrides, mannich bases, imines and the like were used for the purpose of curing epoxy resins at various temperatures. Till date, amines were found to be the most suitable hardener for the purpose of curing epoxy resins at low temperature. While forming composite materials, the rate of curing of the epoxy matrix depends upon the properties of the fibre and hence, the curing rate provided by different curing agents will change, thereby modifying the mechanical properties of the final composite material. In this work, phenalkamine, polyamides and the blend of both phenalkamine and polyamide were used to cure the epoxy resin reinforced with jute fibre, at the room temperature to study the variation in mechanical properties over the range of time. The rate of cure was studied to optimize the best curing agent among the chosen hardeners for epoxy resin on jute reinforcement. The composite sample was studied for its tensile and flexural properties. Also, the load withstanding ability of the composite samples at various temperatures was determined by performing heat deflection test. The Fractography of the loaded sample was studied using scanning electron microscopy.